1997
DOI: 10.1177/088626097012005008
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Elements of Self-Defense and Objective Versus Subjective Instructions on Jurors' Verdicts for Battered Women Defendants

Abstract: Battered woman defendants' claims of self-defense have often been viewed as not fitting the classic definition of self-defense. Vignettes of a legal case varied the explicitness of the threat made to the woman by her partner before she killed him, whether she had the opportunity to retreat, and objective versus subjective instructions by the judge. College students (N = 399) chose a verdict, identified variables that influenced their verdicts, and completed attitudinal measures. The opportunity for retreat inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 19 publications
2
26
2
Order By: Relevance
“…Finally, although some prior research showed no effect of participant gender (Cheyne & Dennison, 2005) the present study supports the findings of Follingstad et al (1997) and Schuller et al (1994) that women generally have lower guilt ratings and are more prodefendant than are men in cases in which a battered woman kills her abuser. In addition to the aforementioned interaction of gender and delay on verdict, sleeping status seemed to have a differential effect on men and women's judgments related to the defendant.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Finally, although some prior research showed no effect of participant gender (Cheyne & Dennison, 2005) the present study supports the findings of Follingstad et al (1997) and Schuller et al (1994) that women generally have lower guilt ratings and are more prodefendant than are men in cases in which a battered woman kills her abuser. In addition to the aforementioned interaction of gender and delay on verdict, sleeping status seemed to have a differential effect on men and women's judgments related to the defendant.…”
Section: Discussionsupporting
confidence: 82%
“…First with regard to sleep status, it is expected that conviction rates, guilt ratings, and provictim sentiments (e.g., victim's emotional distress and sympathy toward victim) will be higher while prodefendant sentiments (e.g., anger toward victim and sympathy toward defendant) will be lower when the victim is described as sleeping than when the victim is described as awake. This prediction is based on attribution theories that suggest participants will consider blame and responsibility of the victim and defendant in making decisions about the case (Alicke, 2000), and on the findings of previous research (e.g., Follingstad et al, 1989Follingstad et al, , 1997Terrance et al, 2000).…”
Section: The Present Studymentioning
confidence: 99%
See 3 more Smart Citations